2016
DOI: 10.3847/1538-4357/834/1/37
|View full text |Cite
|
Sign up to set email alerts
|

The Concentration Dependence of the Galaxy–halo Connection: Modeling Assembly Bias With Abundance Matching

Abstract: Empirical methods for connecting galaxies to their dark matter halos have become essential for interpreting measurements of the spatial statistics of galaxies. In this work, we present a novel approach for parameterizing the degree of concentration dependence in the abundance matching method. This new parameterization provides a smooth interpolation between two commonly used matching proxies: the peak halo mass and the peak halo maximal circular velocity. This parameterization controls the amount of dependence… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
168
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 161 publications
(180 citation statements)
references
References 74 publications
12
168
0
Order By: Relevance
“…The SHMR ofHudson et al Figure 11, middle panel, the scatter for galaxies above and below the transition mass is 0.18 M log * s = dex and 0.33 dex respectively, in agreement with simulations (Rodrí-guez-Puebla et al 2015; Gu et al 2016), although the concerned halo masses are measured within much larger radii than our own total masses. This also matches typical observational estimates of SHMR scatter ranging from 0.15 to 0.35 dex (Yang et al 2009;More et al 2011;Leauthaud et al 2012;Behroozi et al 2013b;Reddick et al 2013;Tinker et al 2013;Kravtsov et al 2014;Lehmann et al 2017). Most of these studies used M vir or M 200 for their SHMRs.…”
Section: Stellar-to-total Mass Relationsupporting
confidence: 65%
“…The SHMR ofHudson et al Figure 11, middle panel, the scatter for galaxies above and below the transition mass is 0.18 M log * s = dex and 0.33 dex respectively, in agreement with simulations (Rodrí-guez-Puebla et al 2015; Gu et al 2016), although the concerned halo masses are measured within much larger radii than our own total masses. This also matches typical observational estimates of SHMR scatter ranging from 0.15 to 0.35 dex (Yang et al 2009;More et al 2011;Leauthaud et al 2012;Behroozi et al 2013b;Reddick et al 2013;Tinker et al 2013;Kravtsov et al 2014;Lehmann et al 2017). Most of these studies used M vir or M 200 for their SHMRs.…”
Section: Stellar-to-total Mass Relationsupporting
confidence: 65%
“…Observationally, Lehmann et al (2017) show that low redshift clustering measurements from SDSS prefer a moderate amount of concentration dependence (more than would be indicated by matching galaxy luminosity to the peak halo mass, and less than would be indicated by matching to the peak halo circular velocity). Defining the halo velocity as Lehmann et al (2017) found that the scatter in stellar mass was minimized at σ = 0.17 +0.03 .…”
Section: Dependence Of Scatter On Halo Velocity Definitionmentioning
confidence: 89%
“…Luminosity Scatter σM ∼ unif(0, 2) dex Conservative upper limit (Lehmann et al 2017;Garrison-Kimmel et al 2017a).…”
Section: Free Parameter Prior Distribution Motivationmentioning
confidence: 99%
“…The prior on the faint-end slope is a non-informative Jeffreys prior (Jethwa et al 2018). The upper limit on the luminosity scatter is chosen to be very conservative; for example, Lehmann et al (2017) find that abundance matching scatter at the luminosity scale of the brightest systems used in our analysis is less than ∼ 0.25 dex. For M 50 , we set the lower limit of the prior based on the resolution limit of our simulations, which is a maximally conservative choice from the perspective of the inferred upper limit on this quantity.…”
Section: B2 Priorsmentioning
confidence: 99%